Microbiological and molecular techniques for the identification of Salmonella sp in the poultry industry: a systematic scoping review - Mondragón G., Valentina (2022)
A systematic review of the diagnostic methods described in the literature for the identification and characterization of species of the genus Salmonella was carried out. The review was carried out using publications from 2015 to 2021 registered in the NCBI/PubMed, ScienceDirect, Scopus, SciELO, Google Scholar and Springer databases and applying the PRISMA methodology. In total, 61 articles were analysed, grouping the data according to country of origin, type of sample, technique, microbiology protocol and genes used in molecular tests. The microbiology protocols are based on performing pre-enrichment in peptone water and enrichment in tetrathionate (TT) and Rappaport-Vassiliadis (RV) broths, especially with faecal or environmental samples, to subsequently carry out isolations in selective and differential media. The identification of some Salmonella sp serovars that cause disease in poultry is mainly done with molecular techniques such as conventional PCR and multiplex PCR, based on the detection of genes such as invA, hilA, fliC, sefA, spvC, pefA, speC y glgC. Molecular tools are an alternative to traditional microbiology and serotyping techniques with the White-Kauffmann-Le Minor methodology, as they require less time and can identify serovars; however, microbiological tools such as enrichment contribute to the step prior to the use of other diagnostic tools.